SOCIALIZATION OF SELF CARE TOGA AND ACUPRESSURE AT GADING HEALTH CENTER IN SURABAYA - Ario Imandiri; Maya Septriana (Darmabakti Cendekia: Journal of Community Service and Engagements, 2019)
Background: The  community  made  various  efforts to  be  able  to  overcome  the health complaints that they experienced, whether it was done alone by people who experienced health complaints or by healthy families. Efforts made by the community in overcoming health complaints suffered include self-treatment based on the knowledge they have by massage or consuming materials or processed from plants or animals, conducting consultations or examinations on traditional and medical health facilities, and can also bring in officers home health. Purpose: Increasing public knowledge regarding how to process traditional medicines and independent acupressure. Method: Providing knowledge to the Independent Care Cadres of Gading Surabaya Health Center regarding how to process traditional medicines and independent acupressure through demonstration of making traditional medicines and independent acupressure. Results: The activity of Independent Care of Family Medication and Acupressure Care for Cadre groups in Gading Surabaya Health Center went well. The cadre welcomed the program and they participated in the coaching activities actively. Conclusion: The Independent Care of Family Medication and Acupressure care for Cadre groups coaching program in Gading Surabaya Health Center is very beneficial for the community in overcoming minor ailments without taking chemical drugs.